The Dynamic Role of Higher Education in The Twenty-First Century: A Critical Approach Towards the Pressing Issues and Possible Solutions - Hong, Chengwen; Fawad Ullah; Luqman Hakeem; Wen, Sanmei (Future Science / FSH-PH Publications, 2023)
Higher education institutes create cohesive and fair societies and thus expect different outcomes in diverse geographical areas. However, in the twenty-first Century, they face issues which need solutions. This critical perspective paper traces the motifs and expected outcomes of higher education in ancient civilizations and analyses the changing roles of teachers and students in the contemporary era. This paper is qualitative and adopts the critical approach methodology to investigate, highlight and propose solutions to several unique issues faced by the higher education system in the contemporary era. This paper brings significant horizons and reveals critical insights about quality higher education.